EFL Teachers’ Strategies in Motivating Low-Achieving Learners in Online Class - Zulkhoir Siregar; Johannes Ananto Prayogo; Utari Praba Astuti (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2023)
This study attempts to investigate EFL teachers’ strategies in motivating low-achieving learners in online classes from the perspective of twenty-five English teachers and thirty low-achieving learners. The data were collected through a questionnaire and a semi-structured interview. The result of the study revealed that there were some foremost motivational teaching strategies applied by EFL teachers to deal with low-achieving learners during online classes; monitoring students’ activities, showing the importance of English, clarifying difficult topics, caring about students’ learning progress, and explaining topics clearly and specifically.